Reconceptualizing Pesantren as Living Educational Ecosystems through Gus Mus' Humanistic Pedagogy - Moh. Nadhif; Akhmad Sirojuddin; Ali Wafa; Muhammad Najib; Salman Khalid bin Othman (Journal of Pesantren and Diniyah Studies, 2026)
This study reconceptualizes pesantren as a living educational ecosystem through the humanistic pedagogy of KH. Ahmad Mustofa Bisri, widely known as Gus Mus. The main problem addressed is that previous studies often describe pesantrens as religious institutions, cultural transmitters, or moral communities. Still, they rarely explain how a pesantren can operate as a humanity-centered educational system grounded in a clear analytical paradigm. This qualitative documentary study analyzes Gus Mus' selected writings, recorded public messages, and scholarly literature on pesantren, humanistic education, and educational ecology. The analysis follows document analysis, thematic coding, theoretical triangulation, and conceptual model building. The findings show that Gus Mus' thought functions as an analytical lens through four operational values: humanity as the aim of learning, rahmah as the ethic of relation, humility as the discipline of self, and social piety as the measure of knowledge. These values illuminate pesantren as an ecosystem where kyai leadership, sanad, adab, communal discipline, daily rituals, kitab learning, and service practices interact to form moral agency. The study proposes a human-centered pesantren educational model that links value input, ecosystem processes, reflective mediation, and humanistic output. This model contributes to pesantren studies by shifting the focus from institutional description to an operational theory of lived human formation.